Cytogenetic and comparative genomic hybridization study of Indian myelodysplastic syndromes - Kawankar, Nikesh; Jijina, Farah; Ghosh, Kanjaksha; Vundinti, Babu Rao (Cancer epidemiology, 2011)
Introduction: Myelodysplastic syndromes (MDSs) are clonal stem cell disorders characterized by cytopenias, dysplasia in one or more cell lineages and ineffective hematopoiesis and are associated with significant morbidity and mortality due to bone marrow failure or evolution to acute myeloid leukemia. Clonal chromosomal abnormalities are detected in 40–60% of patients. Multiple recurrent chromosomal aberrations have been identified by cytogenetics including fluorescence in situ hybridization (FISH) which is now widely recognized as one of the most important diagnostic and prognostic markers in MDS. Methods: Conventional cytogenetics by GTG-banding, FISH, comparative genomic hybridization (CGH) was done on 40 primary MDS subjects. Results: Among 40 subjects, 10 (25%) were abnormal and 30 (75%) showed apparently normal karyotypes with GTG banding and FISH. The various aberrations observed were del 5q−, del 7q−, 20q−, +8. DNA copy number changes including losses (30%) and gains (20%) were detected by CGH in 11 (36.6%) out of 30 karyotypically normal MDS. However chromosome 7 (37%) and 1 (25%) is frequently involved in current study population. Conclusions: This study confirms that the apart from non-random chromosome aberrations, other chromosome regions also involved in the MDS development. The occupational, environmental and geographical variations might be influencing the disease. Furthermore cytogenetic studies are warranted in larger groups of MDS cases to identify newly acquired chromosome aberrations that may aid in cloning new genes involved in the neoplastic process, ultimately helping in the development of targeted therapeutic drugs.